High mitotic index has no prognostic significance in mixed tumor of the vagina - Stolnicu, Simona (Polish Journal of Pathology, 2021)
Mixed tumor of the vagina is a benign neoplasm usually developing in the posterior and distal vaginal wall, close to the hymen, with almost all reported cases exhibiting no or little cellular pleomorphism and rare mitotic activity. The present paper presents a case of a 30 year-old pregnant patient also known to have human immunodeficiency virus (HIV) infection in which a mixed tumor of the vagina was identified and completely surgically removed. Microscopic examination revealed a predominant spindle cell component characterized by high mitotic activity and mild cellular pleomorphism admixed with a minor epithelial component mainly represented by glandular structures lacking atypia and mitoses. Close follow-up showed that the high mitotic index has no prognostic significance in mixed tumor of the vagina, as our patient is well at 3 years after the initial diagnosis.